[Maritza] - Orchid Contreras::::::photographer::: (2005)
Description supplied by photographer: 'Mi cuñada Maritza alistándose para ir a trabajar a las 5:30 AM. Tomamos café porque una buena dosis de cafeína nos mantiene bien despiertas. Trabajamos en le Centro Gereátrico Vineyard Hills.' Translation of description: 'My sister-in-law Maritza getting ready to go to work at 5:30 am. We always drink coffee in the morning to get the caffeine flowing and the day started. We work at Vineyard Hills Health Center Convalescent Home.'